1999
DOI: 10.1063/1.124890
|View full text |Cite
|
Sign up to set email alerts
|

Low-leakage-current metal–insulator–semiconductor–insulator–metal photodetector on silicon with a SiO2 barrier-enhancement layer

Abstract: Articles you may be interested inEnhanced photoresponse of a metal-oxide-semiconductor photodetector with silicon nanocrystals embedded in the oxide layer Appl. Phys. Lett. 90, 051105 (2007); 10.1063/1.2450653 Dual-color ultraviolet metal-semiconductor-metal AlGaN photodetectors Leakage suppression by asymmetric area electrodes in metal-semiconductor-metal photodetectors Very low dark current metal-semiconductor-metal ultraviolet photodetectors fabricated on single-crystal GaN epitaxial layers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In the above design, the gate electrodes and back Ohmic contacts were on different sides of the Si substrates. Both electrodes could be formed on the same side of thin-oxide/Si substrates to fabricate interdigitated metal-insulator-semiconductor-insulator-metal (MISIM) photodetectors ( Figure 14 ) [ 45 , 52 ]. Such a structure could be compared with the MSM structure with the same metal pattern, and then the advantages of the insertion of an insulator layer became obvious.…”
Section: Mis Visible-to-near-ir Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above design, the gate electrodes and back Ohmic contacts were on different sides of the Si substrates. Both electrodes could be formed on the same side of thin-oxide/Si substrates to fabricate interdigitated metal-insulator-semiconductor-insulator-metal (MISIM) photodetectors ( Figure 14 ) [ 45 , 52 ]. Such a structure could be compared with the MSM structure with the same metal pattern, and then the advantages of the insertion of an insulator layer became obvious.…”
Section: Mis Visible-to-near-ir Photodetectorsmentioning
confidence: 99%
“…Such a structure could be compared with the MSM structure with the same metal pattern, and then the advantages of the insertion of an insulator layer became obvious. Seto et al showed that the insertion of a thin SiO 2 layer effectively reduced the dark current by a factor of 5.2 [ 52 ]. The increase in the dark current with the increasing bias was weaker.…”
Section: Mis Visible-to-near-ir Photodetectorsmentioning
confidence: 99%
“…8 However, the potential barrier height of metal-semiconductor contact is inherently low, so the dark leakage current is remarkable and power handling capability is also limited. 9 The bandwidth of electromagnetic spectrum determined by the speed with which the photodetector response to variations in the incident optical power. As described above, PIN photodiodes and MSM photodetectors have limited bandwidths because of the junction capacitance.…”
Section: Fig 1 Schematic Of Semiconductor Photodetectorsmentioning
confidence: 99%
“…Several techniques were reported to decrease the dark current. Some of them consists in: depositing a passivation coating over the entire active area, minimizing the charge surface conduction by interface states [3]; minimize the tunneling current due to high electric field under the electrode contact pads, by implementing an insulator layer under the pads area [5][6]; pattern the entire metal over a very thin insulator film, to obtain an effect of barrier enhancement layer, decreasing the thermionic emission current [7]; and construct the MSM device with two different metals, one to each electrode, to obtain higher values of hole and electron barrier heights [8].…”
Section: Introductionmentioning
confidence: 99%